Manajemen keuangan berbasis teknologi digital di lembaga pendidikan Islam - Usman, Lalu Hamdi; Syaharuddin, Syaharuddin; Maujud, Fathul (Al-Liqo: Jurnal Pendidikan Islam, 2024)
The advancement of digital technology has brought significant changes across various sectors, including financial management in Islamic educational institutions. This transformation necessitates a comprehensive exploration of how digital technology can enhance the effectiveness and efficiency of existing financial systems. This study aims to examine the application of technology-driven financial management within Islamic educational institutions. Adopting a qualitative approach through a Systematic Literature Review, the research analyzes publications from 2014 to 2024 sourced from Scopus, DOAJ, and Google Scholar. The findings reveal that digital technology holds substantial potential to improve efficiency, accuracy, transparency, and accountability in financial management practices. However, Islamic educational institutions face several challenges, including inadequate infrastructure, limited human resource skills, and resistance to change. The study concludes that optimizing the adoption of digital technology in financial management can significantly enhance accountability, transparency, and overall institutional performance. Concrete recommendations are provided to address existing challenges and support effective implementation.